Adsorption of tetracycline on Fe (hydr)oxides: effects of pH and metal cation (Cu2+, Zn2+ and Al3+) addition in various molar ratios. Issue 3 (28th March 2018) - Hsu, Liang-Ching; Liu, Yu-Ting; Syu, Chien-Hui; Huang, Mei-Hsia; Tzou, Yu-Min; Teah, Heng Yi
Abstract : Iron (Fe) (hydr)oxides control the mobility and bioavailability of tetracycline (TC) in waters and soils. Adsorption of TC on Fe (hydr)oxides is greatly affected by polyvalent metals; however, impacts of molar metal/TC ratios on TC adsorptive behaviours on Fe (hydr)oxides remain unclear. Results showed that maximum TC adsorption on ferrihydrite and goethite occurred at pH 5–6. Such TC adsorption was generally promoted by the addition of Cu 2+, Zn 2+ and Al 3+ . The greatest increase in TC adsorption was found in the system with molar Cu/TC ratio of 3 due to the formation of Fe hydr(oxide)–Cu–TC ternary complexes. Functional groups on TC that were responsible for the complexation with Cu 2+ shifted from phenolic diketone groups at Cu/TC molar ratio < 1 to amide groups at Cu/TC molar ratio ≥ 1. For the addition of Al 3+, the complexation only took place with phenolic diketone groups, resulting in the enhanced TC adsorption at a molar Al/TC ratio of 1. However, TC adsorption decreased for Al/TC molar ratio > 1 as excess Al 3+ led to the competitive adsorption with Al/TC complexes. For the Zn 2+ addition, no significant correlation was found between TC adsorption capacity and molar Zn/TC ratios.